Qualitative Evaluation of Technical Parameter of Resiliency: A Case Study of Nuwakot District, Nepal - Adhikari, Manoj; Bhattarai, Anupam Raj; Thapa, Ravi (Journal of Institute of Science and Technology, 2020)
The reconstruction work following the 2015 Gorkha Earthquake is being done under the leadership of the National Reconstruction Authority (NRA) by various organizations in coordination with donor agencies and the local people. A detailed study regarding the reconstruction work is necessary to analyze the work done measured in terms of technical, socioeconomic, and sustainability parameters so that the lessons learned from the study could be used in future policymaking and implementation process that aids in achieving an earthquake-resilient community. The study aimed to evaluate the technical parameter of the reconstruction work done in the Nuwakot district until May 2020, according to the Nepal National Building Codes and the latest NRA guidelines. The study was based on qualitative data collected through a Google form survey. The respondents included experts who were working or had worked in different capacities at various organizations involved in reconstruction efforts at the Nuwakot district. The survey covered aspects such as the status of site topography and geology, technical supervision, design and construction, training and capacity building, and use of vulnerable buildings. The study revealed that most of the buildings are compliant with the specified codes/guidelines and are structurally safe. There is a need to improve on the other aforementioned aspects of technical parameters to aid in achieving resiliency.